Fiberoptic laryngoscopy-- experience in a private hospital - Murshed, KM Mamun; Talukder, Md Harun Ar Rashid; Rahman, Habibur; Uddin, AKM Shaif (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Laryngoscopy is a medical procedure used to obtain a view from nose to voice box (larynx). A thin, lighted tube is usedto view the anatomical detailof the nose, nasopharynx, pharynx andvoice box including motion of the vocal cords in fibreoptic laryngoscopy. Biopsy can also be taken from the suspected lesions. The procedure is usually performed as an OPD procedure under local anesthesia. Methodology: This retrospective, cross sectional observational studywas conducted from June 2007 to October 2015 in a private hospital. Results: 12265 patients were examined and 625 patientsunderwent biopsy during the procedure. Among them male was55.39% and female was 44.61%. Findings were revealed normal in 69.80%,benign looking lesionsin 11.61%, suspected growth in 16.87% of the cases.54.24% were histologically positive for malignancy. Conclusion: Fiberopticlaryngoscopyis a very effective in-office or outdoor procedure for examination of the nose, nasopharynx, pharynx and larynxand also for taking biopsy from the suspected lesions under local anesthesia. J Shaheed Suhrawardy Med Coll, December 2015, Vol.7(2); 59-62